Interviewer biases: can first impressions be changed by displaying stereotypical or non-stereotypical behaviour? - Keogh, Jade (Organisational Psychology, 2016)
In South Africa, where there are many recruitment and selection challenges due to scarce skills and education gaps that exist within the country, the employment interview process may contribute to maintaining racial and gender gaps if decision-making is discriminatory. The purpose of the research was to determine whether interviewers base decisions on stereotypical information, and whether interviewer first impressions can be influenced and changed when interviewees display stereotype congruent or incongruent behaviour in the employment interview. A total of 360 psychology students from the University of Cape Town participated in the study. Participants completed one of eight randomly assigned versions corresponding to eight experimental conditions, in which they rated a black male, black female, white male or white female face in terms of competence, likeability and trustworthiness. Participants rated the same face again after receiving additional information portraying the presented person as either assertive or nice. Results revealed that males and females seen as equally likeable and equally competent, although females are seen as more trustworthy than males. White and black individuals are seen as equally competent however; white females rate white individuals as more competent than black individuals. Black individuals are seen as more likeable than white individuals. White individuals rate white faces as more trustworthy than black faces, while black individuals tended to rate black and white faces as equally trustworthy. Competence and trustworthy ratings increased when individuals displayed assertive behaviour, regardless of candidate race or gender. Likeability ratings, however, were influenced by candidate race and gender, and were in line with assumptions about stereotypical behaviour. Results thus indicate that out-group biases still exist, and that being assertive, regardless of whether it is congruent with an individual's race or gender stereotype or not, increases perceptions of competence.